HUBUNGAN ANTARA PERSEPSI SISWA TERHADAP KELUARGA SAKINAH DENGAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM: SURVEI DI SMPN 2 BEKASI TIMUR - Suharyat, Yayat (Turats, 2012)
This study aimed to determine the relationship between students' perception of sakinah families with the motivation to learn Islamic Education in SMP 2 Jl. Khairil Anwar Margahayu 37 East Bekasi. The method used is quantitative survey method with the correlational approach . This study links between students' perception sakinab family as a variable X and motivation of Islamic Education as a variable Y. The population in this study were students of class VII as many as 135 people. While the sample in this study were 57 students and Random Sampling taken. Before testing the first hypothesis tested is test data analysis of normality and homogeneity tests. From this study it can be concluded that the students 'perception of sakinah family has a positive correlation with the motivation of Islamic Education, meaning that if the students' perception sakinah family increases the motivation to study Islamic education will increase.